The a priori of public leadership: Social attributions to public and private leaders in different performance contexts - Laura Hesmert; Fabian Hattke; Rick Vogel (Public Administration, 2021)
Previous scholarship provides little insight into the differences between public and private leadership in people's a priori assumptions about leaders. We advance a socio-cognitive approach and examine how implicit social attributions to leaders are contingent on sector and performance cues. Participants completed the Semantic Misattribution Procedure to reveal implicit associations of traits with leaders in contrasting scenarios. Results show that sector cues affect such attributions, which in turn influence behavioral intentions, but only so in interaction with performance information. We conclude that public leaders earn fewer credits for success or failure than private leaders.
Keywords: 340